PENANGANAN PASCA PANEN BERBAGAI VARIETAS PADI DENGAN RICE MILLING UNIT (RMU) - Ashar, Ashar; Putera, Ikbal (Journal Galung Tropika, 2012)
The purpose of research to see and know the process and the results of post-harvest handling of the various varieties of rice using the Rice Milling Unit (RMU). The experiment was conducted PB on rice plant. Ase ball and Laboratory PT. Sang Hyang Seri (Persero) Sidrap. samples is done by taking 100 grams of grain at random from each of the varieties are varieties Mekongga, Ciliwung, Inpari 7, Ciherang, and Cisantana. Post-harvest rice by using Rice Milling Unit (RMU) that will address the quality of milled rice, rice resulting in a clean, white, shiny, and keep nourishing that have undergone the process as follows: a) The water content of dry grain harvest (GKP) is between 18% - 22%, b) storage of dry grain harvest (GKP) into dry milled grain (GKK) does not exceed 36 hours after the rice is harvested. The results average GKP processed using RMU shows the lowest water content at 22.9% which is the Ciliwung varieties. GKP higher water content, the higher the percentage of empty. The results of average quality rice Broken skin is processed at RMUshows the water content GKP all varieties together is 14%. Results Mean Quality Components Milled Rice, Variety show any degree of polished rice is the same, namely 95%. Mekongga varieties have the highest head rice percentage, ie 97% of the lowest broken rate, namely 2.8%. The percentage is the lowest head rice varieties Inpari 7, which is 79% broken rate is also high at 16%.